Comparative outcomes of laparoscopic lateral suspension, sacrocolpopexy, and transvaginal mesh for advanced apical prolapse: A retrospective cohort study - Guo, Lilu; Li, Xiaodi; Li, Huihua; Wang, Binan; Guo, Haichun; Wu, Jingni (PLOS ONE, 2025)
Objective To compare perioperative outcomes and long-term anatomical/functional efficacy of laparoscopic lateral suspension (LLS), laparoscopic sacrocolpopexy (LSC), and transvaginal mesh (TVM) procedures in women with POP-Q stage III–IV apical prolapse. Methods This retrospective cohort included 98 participants undergoing surgical repair between 1/1/2021 and 30/12/2021: 34 TVM, 35 LSC, and 29 LLS. Concomitant hysterectomy or uterine preservation was performed based on clinical indications. Anatomical outcomes were assessed via Pelvic Organ Prolapse Quantification (POP-Q) measurements, while functional outcomes and quality of life (QoL) were evaluated using Pelvic Floor Distress Inventory Questionnaire (PFDI-20) and Pelvic Floor Impact Questionnaire (PFIQ-7) questionnaires preoperatively and at 2-year follow-up. Multivariable regression adjusted for age, BMI, parity, and surgical approach. Results LLS demonstrated superior perioperative outcomes, including shorter operative time (3.07 ± 0.15 vs. 4.59 ± 0.13 hours for LSC, p < 0.05), reduced blood loss (64.48 ± 4.62 vs. 116.18 ± 8.10 mL for TVM, p < 0.05), and shorter hospitalization (5.17 ± 0.20 vs. 6.21 ± 0.27 days for TVM, p < 0.05). Groin pain incidence was higher in TVM (21% vs. 0% in LSC/LLS, p < 0.05). All groups achieved significant anatomical restoration (POP-Q points p < 0.001) and QoL improvements (PFDI-20: TVM 97.31 → 8.37, LSC 108.92 → 5.76, LLS 110.89 → 6.64; PFIQ-7: TVM 103.86 → 3.45, LSC 113.24 → 9.28, LLS 122.99 → 8.04; p < 0.001). No intergroup differences persisted after adjusting confounders. Notably, TVM participants with uterine preservation reported significantly better PFIQ-7 scores than hysterectomy subgroups (0.96 ± 0.52 vs. 6.60 ± 3.46, p < 0.05), whereas LSC/LLS showed no such disparity. Conclusion LLS, LSC, and TVM effectively restore anatomy and QoL in advanced apical prolapse, with LLS offering optimal perioperative safety. Uterine preservation during TVM enhances postoperative satisfaction, suggesting individualized surgical planning is critical. Long-term complications and durability require further investigation.